Economic benefits to farmers of six years of application of an insecticidal 'pour-on' to control tsetse in Ghibe, southwest Ethiopia - Mulatu, W.; Swallow, B.M.; Rowlands, G.J.; Leak, S.G.A.; D'Ieteren, G.D.M.; Nagda, S.M. (OAU/STRC, 1999)
A tsetse control campaign using an insecticidal cypermethrin "pour-on" applied monthly to village Zebu cattle in Ghibe in southwest Ethiopia has been in operation for over six years. For four of these years farmers have paid a cost-recovery price for each animal given treatment. Relative densities of tsetse and biting flies fell by 95 percent during the second year of vector control. Despite very high levels of drug resistance, trypanosomal prevalence in adult cattle has been reduced from 41 percent to 16 percent (a reduction of 61 percent) and the number of curative trypanocidal treatments per animal has been reduced by 50 percent. A 57 percent reduction in abortion rate and calf mortality, a 49 percent increase in calf/cow ratio and an 8 percent increase in adult male body weight occurred as a result of tsetse control. Before tsetse control intervention there were fewer than 500 cattle in the area; now, six years later, up to 6500 cattle may be brought for 'pour-on' treatment in a month. The reduced expenditures on trypanocidal drugs more than offset the cost of the pour-on. The additional benefits of increased output of meat (41 percent) and milk (39 percent) led to an overall benefit/cost ratio of 8:1 spread over five years. Two thirds of households own cattle (one third with 1-3 cattle and one third with between 4 and 56 cattle). When the above net benefits are expressed in terms of average household income they represent increases in annual income of between 10 and 34 percent household.